Public forestry planning as the basis of rural governance - Bruña-García, Xabier; Marey-Pérez, Manuel (BOSQUE, 2017)
Social participation in decision-making on land-use management and planning is essential to achieve viable and lasting solutions. Particularly, a joint action by all sectors involved in the development of a tactical and strategic program of natural resources planning, allowing for a consensus final document in which solutions are formulated to the future management of the resources of the region, is being planned. In rural areas, the search for consensus among stakeholders is the most important factor in planning the territory to be the common denominator in all the activities taking place in it. Within the public participation process and the achievement of consensus, it is necessary to have a balanced and representative portion of the various stakeholders in the area. This article discusses the public participation process conducted within the program of forest planning of the A Fonsagrada-Os Ancares district in order to validate this methodology for application in future participatory processes in rural areas.